Virtual Reality Assisted Microteaching For Improving Teaching Skills of Prospective Teachers - Rahmawati, Fanni; Nuraini, Siti; Fitriani, Nur; Afriyanto, Verdyan Nur (Economic Education and Entrepreneurship Journal, 2024)
Education serves as a cornerstone in building a high-quality society, where teachers play a pivotal role in creating effective learning environments and delivering instructional content. However, many prospective teachers face limitations in gaining adequate practical experience before entering real-world teaching scenarios. This study aims to evaluate the effectiveness of Virtual Reality (VR)-assisted Microteaching as an innovative approach to enhance the teaching skills of future educators. Employing a quantitative research design, the study adopts descriptive verification methods through ex post facto and survey approaches. The findings indicate a significant improvement in teaching skills, classroom management, and self-confidence among participants utilizing VR-assisted Microteaching compared to traditional methods. VR technology facilitates realistic and interactive teaching simulations, allowing prospective teachers to engage in diverse scenarios without the stress of real classroom environments. This research underscores the transformative potential of integrating VR technology into teacher education programs to address gaps in conventional training methods and better prepare educators for the complexities of contemporary teaching challenges.DOI: http://dx.doi.org/10.23960/E3J/v7.i2.230-234